Design Thinking Sistem Agribisnis dengan Tinjauan dari Sisi Empathize dan Define - Widhianti, Yulia (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
The agricultural system consists of three main elements: farmers as producers, the supply chain, and consumers, all of which are interdependent. The main challenges in the agribusiness system include supply chain instability, climate change, technological limitations at the farmer level, and information asymmetry between producers, distributors, and consumers. These issues often lead to inefficiencies, resource wastage, and low farmer welfare. Disruptions in one element impact the entire system. The Design Thinking approach is needed in the agribusiness system as it offers innovative solutions based on user needs. This study discusses the Design Thinking concept in the Empathize and Define stages to identify information and explore ideas in designing more effective agribusiness strategies. This approach serves as the foundation for developing the Concurrent Engineering (CE) model, which plays a role in strategic decision-making processes in the agribusiness sector, with a primary focus on agricultural production aspects. The analysis is conducted using the Empathize and Define stages of the Design Thinking method. The study results show that applying the CE concept in agribusiness strategy decision-making, such as crop pattern arrangements and stakeholder coordination, can provide optimal solutions for both farmers and consumers.